Lamotrigine-Associated Skin Rash - J Gordon Millichap (Pediatric Neurology Briefs)
The risk factors and methods of minimizing the occurrence of serious rash during treatment with lamotrigine (LTG) were evaluated by an international panel of experts and by review of published and unpublished reports.